The role of Bhabinkamtibmas in preventing criminal acts of motor vehicle theft at the Tasikmalaya Police - Mukabsi, Eko Putra Irjayanto Zakiri (Police Studies Review, 2024)
This research aims to describe and analyze the role of Bhabinkamtibmas, the factors that influence Bhabinkamtibmas's counseling, as well as the steps taken by Bhabinkamtibmas in efforts to prevent criminal acts of motor vehicle theft in the Tasikmalaya Police jurisdiction. carry out outreach to the community because there is still a lack of knowledge about the prevention of theft resulting in this criminal act occurring. This research was carried out with a qualitative approach, using field research methods, as well as data collection techniques using interviews, observations and document review. The research results found that the role of Bhabinkamtibmas at the Tasikmalaya Police uses management theory. The author found that Bhabinkamtibmas members in the Tasikmalaya Police area had carried out their duties in accordance with Implementing Operational Standards, listened to how to remind and gave Kamtibmas appeals to the community. However, in this research it was found that communication to the public had not been carried out thoroughly so that criminal acts of theft still occurred. Bhabinkamtibmas members themselves have obstacles in the form of inadequate socialization facilities, a lack of Bhabinkamtibmas members and locations that have not been provided with socialization. It is necessary to update facilities and infrastructure so that the performance of Bhabinkamtibmas members can run as it should. Based on the results of the research, the researcher suggests that there should be renewal of facilities and infrastructure as well as additional Bhabinkamtibmas personnel so that the role of Bhabinkamtibmas is more effective in the community and achieves the goal of reducing theft at the Tasikmalaya Police Station.